A Discourse Analysis of Lexical Cohesion on Naila Farhana’s Videos - Winda Wasalwa Batubara; Didin Nuruddin Hidayat; Nida Husna; Alek Alek; Moch. Imam Machfudi (Islamic State Institute of Bengkulu (IAIN) Bengkulu, 2022)
The study sought to investigate the lexical cohesion in three YouTube videos by Naila Farhana,